TEKNOEKONOMI ALAT PEMURNI AIR MENGGUNAKAN ENERGI LISTRIK TERBUANG DI PLTMH GUNUNG SAWUR 1 LUMAJANG - Dedy Eko Rahmanto; Valency Femintasari (JURNAL AGROTEKNOLOGI, 2019)
Water purification is carried out to separate water from minerals in it. One process of water purification is distillation. Water destilator require heat that can be obtained from electricity. The Gunung Sawur 1 Microhydro produces electricity for the surrounding society. But, not all electricity produced by microhydro was used. Excess of electricity from microhydro discharged into dummy load for balancing. The potency of wasted electrical energy can be used for water distillation. The purpose of this research were to make a plan about water purification using wasted electrical energy from microhydro Gunung Sawur 1 and investigate its economic feasibility. This research begun with a survey of potency of wasted electrical energy in microhydro Gunung Sawur 1. The potency of waste electrical energy as the basic to calculate the production capacity of water distillation column. Feasibility study was carried out by using NPV and B/C ratio. The result showed that the potency of wasted electrical energy in microhydro of Gunung Sawur 1 up to 66 kwh/day. The capacity of maximum power of planned distillation column was equal to the maximum power of microhydro dummy load. The production capacity of pure water was about 66 liters a day. The production of water purifier was feasible to do based on NPV value of IDR 30,121,094 and the B/C ratio value of 1.51. Keywords: distillation, microhydro, wasted energy